1993
DOI: 10.1002/hup.470080504
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant therapy with moclobemide in primary care practice

Abstract: A Swiss, open, mdticentre clinical study was conducted in collaboration with 176 general practitioners and internists to evaluate the efficacy and tolerability of moclobemide, an antidepressant belonging to a class of novel reversible MAO-A inhibitors called RIMAs. Six hundred and fifty-four outpatients satisfying the DSM-111 criteria of major depression were recruited and treated for at least four weeks. Efficacy was assessed with the Hamilton Depression Rating Scale (HDRS) and the Hospital Anxiety and Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The HAD has been used to assess patients suffering from major depressive episodes as well as physically ill hospitalised patients [12,13], allowing the severity of these mood disorders to be measured, and therefore its repeated use can provide useful information. The HAD has so far had limited application in the ICU setting; however, a recent study performed in a coronary care unit and comparing three different scales (State-Trait Anxiety Inventory, HAD and Linear Analogue Anxiety Scale) showed that the HAD has the highest test-retest reliability [14].…”
Section: Discussionmentioning
confidence: 99%
“…The HAD has been used to assess patients suffering from major depressive episodes as well as physically ill hospitalised patients [12,13], allowing the severity of these mood disorders to be measured, and therefore its repeated use can provide useful information. The HAD has so far had limited application in the ICU setting; however, a recent study performed in a coronary care unit and comparing three different scales (State-Trait Anxiety Inventory, HAD and Linear Analogue Anxiety Scale) showed that the HAD has the highest test-retest reliability [14].…”
Section: Discussionmentioning
confidence: 99%